Water resources systems management tools (McGraw-Hill, 2005)
This is a unique, integrated approach to water resource systems management and planning. The book provides methods for analyzing water resource needs, modeling, supply reliability, irrigation optimization, and much more. With more and more attention being given to the worldwide interest in sustainability, to the effects of global climate change on future water resources operation and management, as well as public health issues, Dr. Mays has gathered together leading experts in their respective fields offering the latest information on the subject. A fresh approach offering insight for the present generation within the water resources community.